2013
DOI: 10.1523/jneurosci.1007-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Potassium Currents Influence Wallerian Degeneration of InjuredDrosophilaAxons

Abstract: Axons degenerate after injury and in neuropathies and disease via a self-destruction program whose mechanism is poorly understood. Axons that have lost connection to their cell bodies have altered electrical and synaptic activities, but whether such changes play a role in the axonal degeneration process is not clear. We have used a Drosophila model to study the Wallerian degeneration of motoneuron axons and their neuromuscular junction synapses. We found that degeneration of the distal nerve stump after a nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 75 publications
0
29
1
Order By: Relevance
“…Alternatively, synaptic activities in the distal segment may accelerate acute degeneration. However, a recent study in Drosophila showed that following axotomy the distal stump does not fire action potentials (Mishra et al, 2013), arguing against a major role for nerve excitability or synaptic activity in distal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, synaptic activities in the distal segment may accelerate acute degeneration. However, a recent study in Drosophila showed that following axotomy the distal stump does not fire action potentials (Mishra et al, 2013), arguing against a major role for nerve excitability or synaptic activity in distal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these key nodes in the program provides a framework for understanding the mechanism of additional genes and drugs that modulate axon degeneration. Multiple investigators are identifying factors that can affect the degeneration program, and at least a subset is likely to impinge on the NMNAT2/SARM1/MAPK program (Barrientos et al, 2011; Bhattacharya et al, 2012; Brace et al, 2014; Mishra et al, 2013; Wakatsuki et al, 2011). Two exciting recent examples are the identification of the PHR ubiquitin ligase as an important regulator of NMNAT2 levels, and of the kinase AKT as a negative regulator of MKK4.…”
Section: Additional Pathways Modulate the Core Axon Degeneration Programmentioning
confidence: 99%
“…Drosophila is a powerful model for investigating fundamental aspects of neurodegeneration and glial responses to neural damage (Ayaz et al, 2008; Cantera and Barrio, 2015; Etchegaray et al, 2016; Fang and Bonini, 2012; Freeman et al, 2003; Kato et al, 2011; Lee and Sun, 2015; Logan and Freeman, 2007; Liu et al, 2015; Mishra et al, 2013; Rooney and Freeman, 2014; Ugur et al, 2016). Axotomy in adult flies elicits glial reactions that share many cellular hallmarks with mammalian glia responding to neurodegeneration, including altered morphology and increased phagocytic function (Kurant 2011; Logan and Freeman, 2007).…”
Section: Introductionmentioning
confidence: 99%